Analysis of the Effector Activity of Ara h 2 and Ara h 6 by Selective Depletion from a Crude Peanut Extract - Chen, Xueni (2011)
It is important to know the contribution of specific allergens to a complex allergenic extract and to have a dependable method to assess the effector activity of an extract specifically depleted of that allergen. We have previously shown that removal of the major peanut allergen, Ara h 2, from a crude peanut extract (CPE) minimally altered the effector activity of the extract. Here we describe in detail the methodology used to generate specific rabbit anti-peptide antibodies to remove a related peanut allergen, Ara h 6, from CPE and describe an improvement in the RBL SX-38 cell assay used to assess the effector activity of treated extracts. Our results show that although Ara h 2 and Ara h 6 can be selectively removed from a CPE, removal of each alone from a CPE had no significant effect on the effector activity. However, removal of Ara h 2 and Ara h 6 together significantly reduced the effector activity of CPE.